Influence Orientation Entrepreneurship and Innovation on MSME Performance with Superiority Compete Sustainable as Variables Mediation - Muhammad Iqbal; Rina Yuliastuty Asmara (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study examines how entrepreneurial orientation and innovation affect MSME performance through sustainable competitive advantage among MSMEs registered in the SMESCO ecosystem. The research responds to inconsistent empirical findings on whether entrepreneurial orientation and innovation improve performance directly or through competitive mechanisms. Its novelty lies in testing an integrative SMESCO-based model that positions sustainable competitive advantage as a mediator in a structured SEM-PLS framework. A quantitative explanatory design was applied using a survey of 100 MSME owners and managers selected through purposive quota sampling. Data were collected using a five-point Likert questionnaire and analyzed with SmartPLS 4. The results show that entrepreneurial orientation has a positive and significant effect on performance. Innovation also has a positive and significant effect on performance and sustainable competitive advantage. Sustainable competitive advantage positively affects performance, but it does not significantly mediate the effect of entrepreneurial orientation and innovation on performance. These findings indicate that innovation is the most important driver for strengthening MSME outcomes, while long-term competitiveness requires more structured product differentiation, brand development, quality consistency, and customer retention strategies. Practically, SMESCO-assisted MSMEs need to convert innovative activities into measurable market value and sustainable strategic positioning.